2021
DOI: 10.1177/20551029211012208
|View full text |Cite
|
Sign up to set email alerts
|

Patient experiences with videoconferencing as social contact and in follow-up from oncology nurses in primary health care

Abstract: Patients with various forms of cancer often have unmet psychosocial support needs. By interpretative phenomenological approach, this study aimed to acquire a deeper understanding of home-living patients with cancer’s experience and meaning from videoconferencing in oncological nursing follow-up in primary healthcare and contact with networks. Six patients from rural Norway participated. Three themes emerged: (1) From skepticism to videoconferencing-enthusiasm; (2) Oncology nurses ensured tablet mastery and del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Prepandemic studies focused on videoconferencing for palliative care consultation and provision of support between patients, family caregivers, and community-based care clinicians [9][10][11] indicated that VCVs are often preferable for palliative care consultations [11,12], hospice family meetings [13,14], and support groups [15]. Recent studies suggest that patients are similarly satisfied with cancer care received via videoconferencing [16][17][18] and that oncology clinicians are increasingly receptive to videoconferencing and acknowledge its numerous benefits to patients [2].…”
Section: Introductionmentioning
confidence: 99%
“…Prepandemic studies focused on videoconferencing for palliative care consultation and provision of support between patients, family caregivers, and community-based care clinicians [9][10][11] indicated that VCVs are often preferable for palliative care consultations [11,12], hospice family meetings [13,14], and support groups [15]. Recent studies suggest that patients are similarly satisfied with cancer care received via videoconferencing [16][17][18] and that oncology clinicians are increasingly receptive to videoconferencing and acknowledge its numerous benefits to patients [2].…”
Section: Introductionmentioning
confidence: 99%
“…Videoconferencing, although a relatively new technology, is a tool that has seen its use in health sciences expanded over the past decade (Ignatowicz et al, 2019). Research suggests that videoconferencing is a feasible and effective tool to evaluate complex issues such as the treatment of patients with chronic medical conditions (Mallow et al, 2016), including cancer (Nordtug et al, 2021).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Videoconferencing, although a relatively new technology, is a tool that has seen its use in health sciences expanded over the past decade (Ignatowicz et al., 2019). Research suggests that videoconferencing is a feasible and effective tool to evaluate complex issues such as the treatment of patients with chronic medical conditions (Mallow et al., 2016), including cancer (Nordtug et al., 2021). The emergence of the COVID‐19 pandemic required different and novel methods of healthcare delivery, and telehealth has been recognized as one of the prioritized strategies for the World Health Organization since 2020 (Digital Health, 2023).…”
Section: Introductionmentioning
confidence: 99%